Changing Dynamics of Banking Landscape : What Do We Know and What Lies Ahead? - Sardana, Varda; Mohapatra, Amiya Kumar; Singhania, Shubham; Chakrabarti, Deepankar (Prabandhan: Indian Journal of Management, 2024)
Purpose : The primary objective of this paper was to conduct a thorough analysis of the banking sector’s altering dynamics. In doing so, the study answered questions regarding the current picture of the banking landscape as well as the potential future avenues that can be explored by scholars in this domain. Methodology : The research design of this study was based on a systematic literature review (SLR). One hundred sixty-eight documents retrieved from the Scopus database for the period 1990 to 2022 were scrutinized through in-depth content analysis to identify their focal themes and trace the changing shapes of the banking sector. Findings : A total of six broad themes were identified, which portray the various modifications in the banking industry across the globe in the past three decades. These banking adaptations cut across various dimensions such as technology, innovations, consumers, products, as well as bank expansions and have left an indelible mark on the banking operations and models. Implications : The study has implications for banking organizations, facilitating them in understanding, adapting, as well as adopting a forward-looking approach to various upgradations in the banking arena. It would also enable future research scholars to trace the developments in the banking landscape and work on the directions highlighted through the review. Originality : Despite the availability of a large pool of studies on the banking sector, the literature failed to juxtapose changes from the past to the present in areas of emerging technology, regulation, and the like. The current study filled this research gap by providing new insights, as well as by synthesizing and contextualizing the body of existing information on the changing dynamics of the banking sector in order to present a comprehensive overview of the subject.